2016
DOI: 10.1016/j.neurobiolaging.2016.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Identifying postmenopausal women at risk for cognitive decline within a healthy cohort using a panel of clinical metabolic indicators: potential for detecting an at-Alzheimer's risk metabolic phenotype

Abstract: Detecting at-risk individuals within a healthy population is critical for preventing or delaying Alzheimer’s disease. The systems biology integration of brain and body metabolism enables peripheral metabolic biomarkers to serve as reporters of brain bioenergetic status. Using clinical metabolic data derived from healthy postmenopausal women in the ELITE trial, we conducted principal components and k-means clustering analyses of nine biomarkers to define metabolic phenotypes. Metabolic clusters were correlated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 40 publications
2
37
0
Order By: Relevance
“…It is unclear whether metabolic function in E4FAD mice contributed to, resulted from, or was unrelated to their significantly poorer behavioral performance and higher pathology burden under basal conditions. In healthy postmenopausal women, relatively poorer metabolic profile is associated with significantly worse cognitive function (49), a relationship that may be exacerbated by APOE4 genotype (50). Importantly, we found that upon challenge with an obesogenic diet, E3FAD mice showed greater glucose intolerance than E4FAD mice.…”
Section: Discussionmentioning
confidence: 63%
“…It is unclear whether metabolic function in E4FAD mice contributed to, resulted from, or was unrelated to their significantly poorer behavioral performance and higher pathology burden under basal conditions. In healthy postmenopausal women, relatively poorer metabolic profile is associated with significantly worse cognitive function (49), a relationship that may be exacerbated by APOE4 genotype (50). Importantly, we found that upon challenge with an obesogenic diet, E3FAD mice showed greater glucose intolerance than E4FAD mice.…”
Section: Discussionmentioning
confidence: 63%
“…Preclinical studies indicate that during perimenopause, when brain estrogen plummets, the systems required for estrogen activation of cerebral glucose metabolism rates (CMRglc) and suppression of the ketogenic pathways disassemble (18). Following the decline in CMRglc is induction of an adaptive starvation reaction to increase fatty acid metabolism for the generation and utilization of ketone bodies by mitochondria as an alternative fuel (5, 1821). Hypometabolism, reduced mitochondrial function and subsequent oxidative damage are known to promote accumulation of Aß pathology and neuronal dysfunction (22), therefore increasing risk of developing AD later in life.…”
Section: The Role Of Estrogen In the Brainmentioning
confidence: 99%
“…The presence, variability, intensity and duration of neurological symptoms provide potential advance warning signs of impending risk of later health risks, particularly neurodegenerative diseases. Multiple conditions that emerge during aging, such as metabolic dysregulation, cholesterol dyshomeostasis, insomnia, depression, subjective memory complaints and cognitive decline are associated with increased risk of neurodegenerative diseases later in life such as Alzheimer’s(17, 31). Alzheimer’s, like multiple neurodegenerative diseases, is characterized by a long prodromal period, 20 years, during which the disease progresses to clinically diagnosed dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer’s, like multiple neurodegenerative diseases, is characterized by a long prodromal period, 20 years, during which the disease progresses to clinically diagnosed dysfunction. Identifying persons that are at risk for AD while still in a modifiable transition states is critical for reversing or delaying development of Alzheimer’s (31). …”
Section: Introductionmentioning
confidence: 99%